Observation and numerical simulation of a weak waterspout at Hong Kong International Airport. (10th January 2021) - Hon, K. K.; Tse, S. M.; Chan, P. W.; Li, Q. S.
Abstract: A weak waterspout was observed at the Hong Kong International Airport on the morning of June 8, 2020. This paper documents the meteorological observations of this weak system, which was well captured by surface wind sensors and a Doppler weather radar, and this study also investigated the capability of a high‐resolution numerical weather prediction model to simulate the system in a near real‐time configuration. Despite the short‐lived nature of the vortex, the model effectively reproduced the occurrence of a weak vortex around the time the system was observed, although with positional errors of the order of a few kilometres. The simulated vertical cross‐sections of the reflectivity and Doppler velocity were consistent with the actual radar observations and reflected the slanting nature of the micro‐vortex. These results may serve as a useful reference for the study of weak waterspouts worldwide. Abstract : Photo of the reported waterspout affecting a runway construction site at Hong Kong International Airport (source: https://www.thestandard.com.hk/ sectionnews/section/11/219805/waterspout‐spotted‐off‐airport‐in‐rainstorm).